Microstructural control of the transport properties of β-FeSe films grown by sputtering - Ale Crivillero, María Victoria (2019)
We have investigated the correlation between structural and transport properties in sputtered β-FeSe films grown onto SrTiO3 (100). The growth parameters, such as substrate temperature and thickness, have been varied in order to explore different regimes. In the limit of textured thick films, we found promising features like an enhanced Tc ∼ 12K, a relatively high Hc2 and a low anisotropy. By performing magnetoresistance and Hall coefficient measurements, we investigate the influence of the disorder associated with the textured morphology on some features attributed to subtle details of the multi-band electronic structure of β-FeSe. Regarding the superconductor-insulator transition (SIT) induced by reducing the thickness, we found a non-trivial evolution of the structural properties and morphology associated with a strained initial growth and the coalescence of grains. Our results reveal the key effects on the macroscopic electronic behaviour played by the lattice distortion in thin insulating samples and by the grain morphology in thicker superconducting films.